Photosynthetic response to different light intensities and water status of two main Nothofagus species of southern Patagonian forest, Argentina - Peri, Pablo Luis; Martínez Pastur, Guillermo José; Lencinas, María Vanessa (Czech Academy of Agricultural Sciences, 2025)
Net photosynthetic rate (A) and stomatal conductance (gs) of leaves of Nothofagus pumilio and N. antarctica seedlings were measured at different photosynthetic photon flux densities (PPFDs, 20, 150, 250, 500, 750, 1,000, 1,500 and 2,200 µmol/m2/s) and after 60 minutes of shade to determine the rate of photosynthetic induction after seedling transition from low to high PPFD. A and gs were also measured to evaluate the responses to water stress and the tolerance to waterlogging. N. pumilio had higher A values than N. antarctica for all light intensities measured with the maximum value of 16.8 µmol CO2/m2/s saturated at 1,000 µmol/m2/s PPFD. Values of gs for both Nothofagus species also declined as light intensity decreased. The times required for full induction of A were 18 and 27 minutes after the increase of PPFD (full sun) for N. pumilio and N. antarctica, respectively. There was a negative relationship between A and water stress, expressed as pre-dawn leaf water potential (ψlp), where the reduction in gs was the main factor that reduced A in both species. Tolerance to waterlogging was related with changes in A and gs where N. antarctica was more tolerant. These photosynthetic results of Nothofagus leaves to fluctuating light, water stress and waterlogging could be used to estimate the responses of regeneration to environmental conditions under the dynamics of natural stands, after silvicultural practices and for restoration plans.